Art for every home Associated American Artists : 1934-2000 - Seaton, Elizabeth G. 19XX-; Myers, Jane 1955-; Windisch, Gail; Condominas, Laura Duke 1951- (Marianna Kistler Beach Museum of Art, Kansas State University, 2015)
"This book will provide the first comprehensive and critical overview of Associated American Artists (AAA), the commercial enterprise best known as the publisher of prints by Thomas Hart Benton, John Steuart Curry, and Grant Wood. It addresses not only AAA's storied involvement in the sale of American prints via mail-order catalogue, but also its ongoing promotion of American art in a range of mediums over six decades. Through aggressive marketing of studio prints, reproductions of art, ceramics and textiles, and associations with corporate advertisers, AAA sought to bring "original" American art over the threshold of every American home"--
"Published by the Marianna Kistler Beach Museum of Art on the occasion of the exhibition. - "Tour: September 15, 2015-January 31, 2016, Marianna Kistler Beach Museum of Art ... April 19-July 9, 2016, Grey Art Gallery, New York University ... September 16, 2016-January 2, 2017, American Textile History Museum ... January 26-March 26, 2017, Syracuse University Art Galleries ..."--Colophon. - Includes bibliographical references and index
Keywords: Associated American Artists; Geschichte 1900-2000; Geschichte 1934-2000; Geschichte; Kunst; Art, American / Exhibitions / Reproduction; Art, American / Exhibitions / 20th century; Art / Exhibitions / Economic aspects / United States; Art and society / Exhibitions / History / 20th century / United States; ART / Prints; ART / History / Modern (late 19th Century to 1945); ART / American / General; ART / Collections, Catalogs, Exhibitions / Group Shows; USA; Ausstellungskatalog; Ausstellungskatalog -- Marianna Kistler Beach Museum of Art -- 15.09.2015-31.01.2016 -- Manhattan, Kan.